2015
DOI: 10.4209/aaqr.2014.07.0127
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopic and Chemical Characteristics of Bulk Aerosols during Winter and Summer Seasons at a Station in Western Coast of India (Goa)

Abstract: We measured stable isotopic and chemical characteristics of bulk aerosols collected at a coastal station in western India (Goa) between December 2009 and January 2011, to characterize lower tropospheric atmospheric conditions and their influence on particle chemistry during winter and summer seasons. Marked differences were observed in terms of sources and chemical compositions of bulk aerosols. The δ 15 N TN values of winter aerosols (10.8 ± 2.2‰, n = 10) indicate biomass burning contributions in the carbonac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…It is also worthwhile to mention that source‐specific stable carbon isotopic composition of TC from FF‐comb source used in this study is not from the IGP, which therefore introduces some uncertainty. However, source‐specific δ 13 C of FF‐comb from South Asia [ Aggarwal et al ., ; Agnihotri et al ., ; Agnihotri et al ., ] is consistent with the literature data [ Cao et al ., ; Ho et al ., ; Widory , ] and, therefore, may not bias the results in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worthwhile to mention that source‐specific stable carbon isotopic composition of TC from FF‐comb source used in this study is not from the IGP, which therefore introduces some uncertainty. However, source‐specific δ 13 C of FF‐comb from South Asia [ Aggarwal et al ., ; Agnihotri et al ., ; Agnihotri et al ., ] is consistent with the literature data [ Cao et al ., ; Ho et al ., ; Widory , ] and, therefore, may not bias the results in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Widory et al (2004) reported the value of d 13 C 3.3 to 14.3 9.6 ± 2.8 2.8 to 11.0 6.8 ± 2.4 2.8 to 11.5 7.4 ± 2.7 lg C m -3 (TC) 13.1 to 125.9 53.0 ± 33.6 9.3 to 51.9 27.1 ± 13.2 9.1 to 98.2 32.6 ± 24.9 lg N m -3 (TN) 1.5 to 42.6 14.9 ± 10.8 2.3 to 36.6 9.8 ± 9.7 1.4 to 25.9 9.3 ± 8.2 TC/TN 4.8 to 20.2 9.8 ± 3.7 2.1 to 16.3 9.2 ± 4.0 4.4 to 25.9 11.1 ± 5.7 d 13 OC -26.6 to -24.9 -25.5 ± 0.4 -26.3 to -24.6 -25.3 ± 0.7 -27.3 to -25.0 -26.1 ± 0.7 lg OC m -26.5 ± 0.5 % indicates the other sources (fossil fuel, coal etc.,) of C in ambient urban area. Agnihotri et al (2015) discussed in detail about the end member isotopic values (d 13 C and d 15 N) of major typical sources. The analysis of OC and EC concentrations over Delhi, Varanasi and Kolkata are attributed to the combined effects of traffic emission and biomass burning (including wood burning and crop residue burning).…”
Section: Resultsmentioning
confidence: 99%
“…in both PM 2.5 and PM 10 samples collected in A Coruña during winter. The lower δ 15 N values during summer in A Coruña could also hint a higher contribution of marine nitrogen species (with lighter δ 15 N) at this suburban location(Agnihotri et al, 2015).…”
mentioning
confidence: 91%